Glassy carbon electrode modified with multi-walled carbon nanotubes sensor for the quantification of antihistamine drug pheniramine in solubilized systems - Rajeev Jain; Sanjay Sharma (Elsevier, 2012)
A sensitive electroanalytical method for quantification of pheniramine in pharmaceutical formulation has been investigated on the basis of the enhanced electrochemical response at glassy carbon electrode modified with multi-walled carbon nanotubes in the presence of sodium lauryl sulfate. The experimental results suggest that the pheniramine in anionic surfactant solution exhibits electrocatalytic effect resulting in a marked enhancement of the peak current response. Peak current response is linearly dependent on the concentration of pheniramine in the range 200â1500Â Î¼g/mL with correlation coefficient 0.9987. The limit of detection is 58.31Â Î¼g/mL. The modified electrode shows good sensitivity and repeatability. Keywords: Pheniramine, Sodium lauryl sulfate (SLS), Glassy carbon electrode modified with multi-walled carbon nanotubes (GCE-MWCNTs), Solubilized systems, Voltammetric quantification